KEPEMIMPINAN KETUA PROGRAM STUDI S1 PENDIDIKAN AGAMA KRISTEN DI SEKOLAH TINGGI TEOLOGI EKKLESIA PONTIANAK - Sintikhe Dinanda Gabriella Panjaitan; Wahyudi Wahyudi; Usman Radiana (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe problem studied was leadership of the head of the undergraduate study program. The research method used by researchers is a qualitative approach. Data was collected through interviews, observations, documentation and analyzed through data reduction, data presentation, conclusions or verification. The research results are build good communication, build good motivation and build a solid team. The results of the discussion are 1) The head of the study program builds good communication by conducting light dialogues, holding joint discussions, listening to suggestions and input from lecturers. 2) The head of the study program builds good motivation, namely giving an assessment of the performance of the lecturers, giving awards for the performance of the lecturers, treating the lecturers well and generating the desire to learn from the lecturers. 3) The head of the study program builds a solid team by making an agreement to obey the rules to work effectively. Share responsibilities that are fair and clear and able to adapt to positive changes. The conclusion is that the head of the study program leadership in the leadership process is to build good communication, build good motivation and build a solid team with the lecturers.Keywords: Leadership, Head Of Study Program